2001
DOI: 10.1080/00420980124102
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Walking: The Case of Journey-to-school Trips in Compact Urban Areas

Abstract: An activity-based approach is used to analyse one specific short-trip purpose that has persistently frustrated transport analysts trying to induce more walk, cycle or public transport based trips. This study of the journey-to-school trip is motivated by a general consensus that, to effect a more sustainable transport system, there is a necessity to reduce car use (especially for short trips). Resistance to modal transfer from cars has been shown to be embedded in various psycho-social obstacles which are not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(48 citation statements)
references
References 15 publications
0
46
0
2
Order By: Relevance
“…For example, Schlossberg et al (2006) surveyed parents of children at four Oregon middle schools and found that parents have "compelling reasons for driving their children to school that are unrelated to urban form or distance" (Schlossberg et al, 2006), p. 344). This illustrates how a child's travel mode choice is very much a part of the household decision-making process (Black et al, 2001). Household trip interdependencies, especially the linkage between trips to school and work (Black et al, 2001) often play a large role in the decision.…”
Section: Household Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Schlossberg et al (2006) surveyed parents of children at four Oregon middle schools and found that parents have "compelling reasons for driving their children to school that are unrelated to urban form or distance" (Schlossberg et al, 2006), p. 344). This illustrates how a child's travel mode choice is very much a part of the household decision-making process (Black et al, 2001). Household trip interdependencies, especially the linkage between trips to school and work (Black et al, 2001) often play a large role in the decision.…”
Section: Household Characteristicsmentioning
confidence: 99%
“…This illustrates how a child's travel mode choice is very much a part of the household decision-making process (Black et al, 2001). Household trip interdependencies, especially the linkage between trips to school and work (Black et al, 2001) often play a large role in the decision. For example, Schlossberg et al (Schlossberg et al, 2006) found that the ease of dropping child off on way to work was cited by 41% of parents surveyed who drove their kids to school.…”
Section: Household Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations